Review of Maternal Deaths in Sudan from 2010–2012: Achievements and Challenges - Umbeli T; Eltahir S; Mirghani SM; Kunna A; Hussein IMA (Disease and Health: Research Developments Vol. 1, 2024)
Background: Maternal deaths and disabilities remain a major public health problem in developing countries, in spite of the efforts of many international and developmental health agencies. Despite the worldwide commitment to improving maternal health, measuring, monitoring and comparing mortality estimates remain a challenge. Maternal death review (MDR) is a tool used to measure the maternal mortality ratio (MMR) and to improve the quality of obstetric care. Objectives: This study was done to assess maternal mortality and to identify underlying causes during 2010-2012. Materials and Methods: Facility and community-based maternal death review was conducted during three years in Sudan to study maternal mortality. All women who died in the hospital or community from pregnancy-related conditions were included. Data was collected by trained registrars and healthcare providers. National and state’ maternal death review committees were established. A focal person for each state, health facility and locality was nominated. Notification of maternal deaths was done by telephone, followed by a review of all notified maternal deaths using a structured format. Data was analyzed using a microcomputer, with SSPS, version 18.0. Results: Maternal mortality ratios remained unacceptably high across much of the developing world. This study showed that, over three years, 2933 maternal deaths were notified, out of 1509354 Live births (LB). MMR was 194/ 100000 LB, with different variation between states. Facility maternal deaths were 2503 (85.3%) and community deaths were 430 (14.7%), reviewed formats were 2859 (97.5%). Direct obstetric deaths were 1845 (64.5%), mainly due to haemorrhage 884 (30.9%), eclampsia 383 (13.4%) and sepsis 321 (11.2%). Indirect causes were 1014 (35.5%), 363 (12.7%) due to hepatitis and 197 (6.9%) to anemia. Most of the hospital deaths 1947 (77.9%); admitted late from home, 2462 (73.4%) were critically ill and 1484 (60.3%) died within 24 hours. Conclusion: Home delivery, late presentation, unavailability of blood and poor referral system, are the main factors behind maternal deaths. Maternal death review has to be integrated within the health management information system (HMIS) with a strong commitment of various stakeholders. Slow implementation of suitable interventions at the country level to utilize MDR recommendations for reducing MMR and lack of operational plans and suitable framework for monitoring and evaluation of MDR progress.